Kinetics of yttrium dissolution from waste ceramic dust - Stopić, Srećko R.; Friedrich, Bernd G. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Yttrium is a silvery transition metal and has similar chemical properties to lanthanoids. Because of this similarity, yttrium belongs to rare earth elements. Ytttrium and yttrium oxide are mostly used in fluoroscent lamps, production of electrodes, in electronic filters, lasers, superconductors and as additives in various materials to improve their properties. Yttrium is mainly recovered from the minerals monazite [(Ce,La,Th,Nd,Y)PO4] and xenotime YPO4.The presence of radioactive elements such as thorium and uranium in the ore makes it difficult to separate yttrium oxide from primary raw materials. Environmental regulations are getting stricter every year, thus increasing the risk of lacking the supply of rare earths. Therefore, recovery of yttrium oxide from secondary sources such as red mud, coatings from ceramic industry and phosphors is extremely important. The main aim of this study is to examine the yttrium dissolution kinetics from waste ceramic dust using hydrochloric acid.
Keywords: yttrium; recycling; hydrometallurgy; ceramics